Project Management Maturity Model (PMMM) in educational organizations - Demir, C.; Kocabas, Ibrahim (Elsevier Science Bv, 2010)
Project Management Maturity Model (PMMM) is getting popular because of its versatility and its ability to control time and cost most efficiently. More and more organizations have embraced Project management as a key strategy for remaining competitive in today's highly competitive business environment. The PMMM allows the organization to identify what steps must be taken, what deeds must be accomplished and in what sequence to realize meaningful and measurable results. The purpose of this study is to see whether PMMM can be used in educational organizations. By the help of maturity model, educational organizations can determine their capability to deliver high education on a five scale. A literature review have been made about maturity model and it has been discussed how to use maturity level in educational organizations in this paper. In order to improve educational organizations' effectiveness, it should become a strategic part of annual plan of the organization. (C) 2010 Elsevier Ltd. All rights reserved
1st World Conference on Learning, Teaching and Administration (WCLTA) -- OCT 29-31, 2010 -- Amer Univ, Cairo, EGYPT
Keywords: Project Management; Maturity Models; Project Management Maturity Model; Capability Project Management; Educational Organizations